The Impact of Makha Bucha Festival at Prasat Hin Wat Phu, Champasak Province on the People Life’s Way, Champasak Province, Lao People’s Democratic Republic - Vongthathongdam, Phra Simeuang; Panyapa, Assoc. Prof. Dr. Rattana; Khejornsa, Asst. Prof. (Special) Ruangdet (Journal for Developing the Social and Community, 2019)
The purpose of this research was to study the participation of the Makha Bucha Festival at Prasat Hin Wat Phu, its impact in the surrounding communities of Prasat Hin Wat Phu, and the comparison of public opinion about its impact classified by sex, education, age, settlement in the area and career. The samples were 282 people in the villages surrounding Prasat Hin Wat Phu, Champasak Province, Lao People’s Democratic Republic. The questionnaire was used as a tool for data collection. The statistics used in this analysis were average, percentage, standard deviation, t-test and F-test (One way ANOVA). The results of the study showed that: 1) Public participation was at a medium level, 2) Overall average of its impact on the people’s way of life was at a medium level, 3) The comparison of the public opinions about its impact on the way of life of the people classified by age, education, the settlement is the area and career were significantly different at the.05 level, but not different by gender.